2018
DOI: 10.1186/s40729-018-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of orthodontic mini implants for en masse retraction in the maxilla: a systematic review and meta-analysis

Abstract: Background/aimRetraction of the upper incisors/canines requires maximum anchorage. The aim of the present study was to analyze the efficacy of mini implants in comparison to conventional devices in patients with need for en masse retraction of the front teeth in the upper jaw.Material and methodsAn electronic search of PubMed, Web of Science, and EMBASE and hand searching were performed. Relevant articles were assessed, and data were extracted for statistical analysis. A random effects model, weighted mean dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 58 publications
1
35
0
6
Order By: Relevance
“…noticed gain of anchorage with anchorage from mini-implants. [ 19 ] These results were in similar to our study.…”
Section: Discussionsupporting
confidence: 93%
“…noticed gain of anchorage with anchorage from mini-implants. [ 19 ] These results were in similar to our study.…”
Section: Discussionsupporting
confidence: 93%
“…Since the introduction of palatal implants and orthodontic mini‐screws in the mid‐1990s (Kanomi, ; Melsen & Costa, ; Park, Bae, Kyung, & Sung, ; Wehrbein, Glatzmaier, Mundwiller, & Diedrich, ; Wehrbein, Merz, Diedrich, & Glatzmaier, ), skeletal anchorage is increasingly employed to enhance orthodontic anchorage. In recent years, therapeutic advantage could be demonstrated for several indications including en‐masse retraction of the front (Becker, Pliska, et al, ), skeletally anchored protraction of the maxilla in early class III treatments (Meyns, Brasil, Mazzi‐Chaves, Politis, & Jacobs, ; Rodriguez de Guzman‐Barrera et al, ), and for the mesialization and distalization of molars (Becker, Wilmes, Grandjean, Vasudavan, & Drescher, ; Wilmes, Katyal, & Drescher, ).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated for several indications including en-masse retraction of the front (Becker, Pliska, et al, 2018), skeletally anchored protraction of the maxilla in early class III treatments (Meyns, Brasil, Mazzi-Chaves, Politis, & Jacobs, 2018;Rodriguez de Guzman-Barrera et al, 2017), and for the mesialization and distalization of molars (Becker, Wilmes, Grandjean, Vasudavan, & Drescher, 2018;Wilmes, Katyal, & Drescher, 2014).…”
mentioning
confidence: 99%
“…In a systematic review published in 2014, Jambi et al23 showed that the mean mesiodistal movement of the upper first permanent molars in the control group ranged from 1.47 to 3.22 mm and was 1.68 mm lower (2.27 to 1.09 mm lower) in the TAD group. Some recent meta-analyses and systematic reviews242526272829 confirmed the efficacy of en masse retraction of the anterior teeth in comparison to conventional anchorage or two-step retraction, with the difference in anchorage loss of around 2.5 mm being in favor of en masse retraction with TADs. In our study, the difference in anchorage loss between the TAD group and conventional anchorage group was significant but at a lower level (0.74 mm).…”
Section: Discussionmentioning
confidence: 94%